Pathogens and Pathogenesis in Wheezing Diseases in Children Under 6 - Tang, Yongjun; Yang, Yaxiong; He, Ruohui; Huang, Rong; Zheng, Xiangrong; Liu, Chentao (Frontiers in Oncology, 2022)
Few studies had comprehensively assessed the roles of cytokines production in wheezing pathogenesis. Therefore, we undertook a retrospective study to determine the association of wheezing episodes and cytokines, aimed to provide some light to further investigation. We collected 176 infants from Xiangya Hospital including 122 subjects with first wheezing and 54 subjects with recurrent wheezing. Besides, 52 infants with wheezing diseases from Xiangya Hospital and Hunan Children’s Hospital (26 infants with first wheezing and 26 infants with recurrent wheezing) and compared to 25 normal controls from Xiangya Hospital were also enrolled in our study. Expression of interferon-γ (IFN-γ), interleukin-4 (IL-4), IL-17, IgE, matrix metalloproteinase-3 (MMP-3) and MMP-9 were quantified within serum or plasma in 52 cases and 25 normal controls. The results showed that boys under 3-year-old and infants with allergy history were more likely to develop wheezing diseases. In our cohort, M. pneumoniae caused a greater proportion of wheezing infants than expected. The expression of IgE, IL-4, IFN-γ, MMP3, MMP9 and IL-17 were increased in wheezing group compared to normal controls. The difference of MMP9 level between first and recurrent wheezing was found in cases from Hunan Children’s hospital. There was an altered cytokine production in infants with wheezing diseases which was quite similar to asthma pathogenesis. Sex, age, pathogen infection and inflammation in our study were also risk factors for wheezing diseases.